Use of an Immobilized Monoclonal Antibody to Examine Integrin &agr;5&bgr;1 Signaling Independent of Cell Spreading - Bao Wenjie; Strömblad Staffan (Biological Procedures Online, 2002)
Cell attachment to the extracellular matrix (ECM) engages integrin signaling into the cell, but part of the signaling response also stem from cell spreading (3). To analyze specific integrin signaling-mediated responses independent of cell spreading, we developed a method engaging integrin signaling by use of an immobilized anti-integrin monoclonal antibody (mab) directed against the fibronectin (FN) receptor integrin &agr;5&bgr;1. ECV 304 cells were plated onto FN or immobilized mab JBS5 (anti-integrin &agr;5&bgr;1) or onto poly-L-lysin (P-L-L), which mediates integrin-independent attachment. Cells attached and spread on FN, while cells on JBS5 or P-L-L attached but did not spread. Importantly, plating onto FN or mab JBS5 gave rise to identical integrin-induced responses, including a down-regulation of the cyclin-dependent kinase (Cdk2) inhibitors p21CIP1 and p27KIP1, while attachment to P-L-L did not. We conclude that engagement of the FN-receptor integrin &agr;5&bgr;1 induces integrin signaling regulating the Cdk2-inhibitors independent of cell spreading and present a method for how integrin signaling can be analyzed separate from the effects of cell spreading.